Pengetahuan, Kesadaran, dan Praktik Orang Tua tentang Resistensi Antibiotik Pada Anak di Sampang, Kabupaten Cilacap - Pepi Nur Wijayanti; Silma Kaafah; Siti Setianingsih (Farmasains : Jurnal Ilmiah Ilmu Kefarmasian, 2025)
Inappropriate use of antibiotics in children contributes to antibiotic resistance. Parents in Cilacap have limited knowledge and awareness of it. This study aimed to describe the knowledge, awareness, and practices of parents regarding antibiotic resistance in 0-11 years old children in Cilacap, as well as to explore the relationship of those aspects and the respondents’ characteristics. The research used a descriptive cross-sectional approach in Sampang District, Cilacap Regency, conducted in May 2024 with 96 respondents selected through cluster random sampling with inclusion criteria. The respondents were parents of 0-11 years old children, with or without antibiotic treatment history, and willing to participate by completing questionnaires. Results showed that 63.5% respondents had high knowledge, 66.7% respondents had high awareness, and 65.6% respondents had good practices. The results indicated that age and education significantly influenced knowledge, awareness, and practices, with p-values <0.05. Meanwhile, gender and occupation showed no significant effect, as evidenced by p-values >0.05. The findings indicate that parents in Sampang District generally demonstrate high knowledge and awareness, as well as good practices concerning antibiotic resistance in children. However, certain demographic factors, particularly age and education, remain influential in shaping these outcomes.